Atmospheric electrical field suppression in the time of the M =4.1 Sousel earthquake (Portugal) - Silva, Hugo Gonçalves (2012)
In recent years different phenomena associated with seismic events have been referred in the literature. These include: unusual ultra-low-frequency electromagnetic emissions [1]; anomalies in very-low and low-frequencies radio transmissions [2]; variation of the ionosphere total electron content [3]; and anomalous levels of different geochemical elements (in particular radon) in the earthquake preparation zone have been reported [4]. Interestingly, an innovative paper has shown the possibility of enhanced air ionization, with consequent atmospheric electricity perturbations, in the preparatory stage of seismic events [5]. It relates possible atmospheric electrical field anomalies during the earthquake preparation with surface air ionization through radon emanations. In fact, this work presents the observation of a significant suppression of the vertical component of the atmospheric electrical field that occurred in Évora (Portugal) soon before the M = 4.1 Sousel earthquake of 27 March 2010. The observation is reported, followed by the analysis and interpretation. Preliminary conclusions and plans for future works are drawn. References [1] T. Bleier et al., Nat. Hazards Earth Syst. Sci. 9, 585, 2009. [2] P.F. Biagi, et al., Nat. Hazards Earth Syst. Sci. 9, 1551, 2009. [3] V. Chauhan, et al., Journal of Geodynamics 48, 68, 2009. [4] J.P. Toutain and J.C. Baubron, Tectonophysics 304, 1, 1999. [5] R.G. Harrison, et al., J. of Atmospheric Solar-Terrestrial Phys. 72, 376, 2010.